2019
DOI: 10.2196/14967
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Intervention Addressing Alcohol Use Problems (the “Daybreak” Program): Quasi-Experimental Randomized Controlled Trial

Abstract: BackgroundAlcohol use is prevalent in many societies and has major adverse impacts on health, but the availability of effective interventions limits treatment options for those who want assistance in changing their patterns of alcohol use.ObjectiveThis study evaluated the new Daybreak program, which is accessible via mobile app and desktop and was developed by Hello Sunday Morning to support high-risk drinking individuals looking to change their relationship with alcohol. In particular, we compared the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Recovery-specific sites that operate on monthly fee-for-use models are outside the scope of this review. Though given the paucity of data on benefits of recovery-specific social network site participation, it is worth mentioning that longitudinal research has shown that greater engagement on Daybreak (formerly Hello Sunday Morning), including more posts and comments, is associated with better drinking outcomes over time (Kirkman et al, 2018;Tait et al, 2019).…”
Section: Recovery-specific Social Network Sitesmentioning
confidence: 99%
“…Recovery-specific sites that operate on monthly fee-for-use models are outside the scope of this review. Though given the paucity of data on benefits of recovery-specific social network site participation, it is worth mentioning that longitudinal research has shown that greater engagement on Daybreak (formerly Hello Sunday Morning), including more posts and comments, is associated with better drinking outcomes over time (Kirkman et al, 2018;Tait et al, 2019).…”
Section: Recovery-specific Social Network Sitesmentioning
confidence: 99%
“…Of the 50 interventions, one gave evidence of addressing all benchmark criteria (Loh et al, 2018). Two intervention provided evidence of addressing seven of the criteria (Yam et al, 2017;Rundle-Thiele et al, 2015) while 12 interventions demonstrated clear evidence of addressing 4 of the benchmark criteria (Adam et al, 2016;Dehlin et al, 2019;Dietrich et al, 2019;Frerichs et al, 2015;Glassman et al, 2018;Khurshid et al, 2015;Pounds et al, 2014;Sanders et al, 2019;Scarapicchia et al, 2015;Shah et al, 2020;Tait et al, 2019;Ullmann et al, 2018). The three most common criteria absent were exchange, competition, and citizen orientation.…”
Section: Benchmark Criteriamentioning
confidence: 99%
“…Toward the end of 2015 HSM closed the first app, and set about designing a new app called Daybreak, which launched in September 2016 (Tait et al, 2019). Daybreak deliberately targets high-risk and dependent drinkers, rather than young binge drinkers.…”
Section: Phase 3: Training Participants and Algorithmsmentioning
confidence: 99%